STEMI telemedicine for 100 million lives. Issue 6 (4th August 2021) - Mehta, Sameer; Grines, Cindy L.; Botelho, Roberto; Fernandez, Francisco; Cade, Jamil; Dusilek, Cesar; Prudente, Mauricio; Cavalcanti, Ricardo; Campos, Carlos; Alcocer Gamba, Marco
Abstract: Background: Developing countries struggle to diagnose and treat ST‐segment elevation myocardial infarction (STEMI) patients in a timely manner, and subsequent outcomes are suboptimal. Methods: The Latin America Telemedicine Network (LATIN) functioned between 2013 to present in four countries—Brazil, Colombia, Mexico, and Argentina. A Hub and Spoke platform was developed to expand access to >100 million population for STEMI care. Patients were triaged at spokes that included small clinics and primary health care centers in remote South American locations. Three telemedicine command sites provided immediate 24/7 electrocardiogram diagnosis and teleconsultation of the STEMI process at 355 centers in four countries. Results: LATIN Spokes (n = 313) screened up to 30, 000 patients per month, and a total of 780, 234 patients over the study period. Telemedicine experts diagnosed 8395 (1·1%) with STEMI, of which a total of 3872 (46·1%) were urgently treated at 47 Hubs. A total of 3015 patients (78%) were reperfused with percutaneous coronary intervention. Time‐to‐telemedicine diagnosis averaged 3·5 min. Average door‐to‐balloon time improved from 120 to 48 min during the study period and overall STEMI mortality was 5·2%. Interpretation: Telemedicine transcends boundaries and enables access to millions of patients for STEMI care. With this initiative, LATIN has created a template for reducing disparities in STEMI management between developed and developing countries.